Acute Pancreatitis Secondary to Hemobilia after Percutaneous Liver Biopsy: A Rare Complication of a Common Procedure, Presenting in an Atypical Fashion. (2nd September 2018) - Mansour, Ramy; Miller, Justin
Abstract : Percutaneous Liver Biopsy is an often-required procedure for the evaluation of multiple liver diseases. The complications are rare but well reported. Here we present a case of a 60-year-old overweight female who underwent liver biopsy for elevated alkaline phosphatase. She developed acute pancreatitis secondary to hemobilia, with atypical signs and symptoms, following the biopsy. She never had the classic triad of RUQ pain, jaundice, and upper GI hemorrhage. There were also multiple negative imaging studies, thus complicating the presentation. She was successfully treated with ERCP, sphincterotomy, balloon sweep, and stent placement. Angiography and transcatheter embolization were not required.